A Review of Significant Contributions of Psychology to Canadian Higher Education - Donald, Janet Gail (Canadian Journal of Higher Education, 1981)
Psychological research in several areas has made or shows the potential to make significant contributions to Canadian higher education. At the most microscopic level, cognition and learning, researchers have examined factors affecting learning, how students organize course material, and how information is processed. The evaluation of learning and the measurement of student abilities in higher education have benefitted from psychological methods. Instruction is a critical process in higher education and research in that area considers the goals and competencies of instruction, the effect of different methods of instruction on learning, and the evaluation of teaching. At a more general level, research into student characteristics covers social and moral development as well as patterns of achievement. At the most global level, the organization and operation of the university, program evaluation is a prominent need and staff development is considered. Overall a review of the research suggests important factors which could affect higher education, but the need for more organized and continued study of these factors and their effects is evident. In-depth study of learning in the university, analysis of student characteristics and their effects on learning, and research on the programs and operation of the university are priorities for future research.